THREE CONTEMPORARY REFORMERS IN ISLAM : THEIR IDEAS ON BEING KHALIFAH OF ALLAH - Allamah Muhammad Iqbal, author 637642; Ali Shari'ati, author 637643; Muhammad Fazl-ur-Rahman, author 345626 (Ampang, Selangor : The Khalifah Institute, 2004)
YBhg. Tan Sri Dr. Salleh bin Mohd Nor